2021
DOI: 10.3390/v13091780
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Derivatives of Platelet-Derived Growth Factor Receptor Alpha Inhibit Cell-Associated Spread of Human Cytomegalovirus

Abstract: Cell-free human cytomegalovirus (HCMV) can be inhibited by a soluble form of the cellular HCMV-receptor PDGFRα, resembling neutralization by antibodies. The cell-associated growth of recent HCMV isolates, however, is resistant against antibodies. We investigated whether PDGFRα-derivatives can inhibit this transmission mode. A protein containing the extracellular PDGFRα-domain and 40-mer peptides derived therefrom were tested regarding the inhibition of the cell-associated HCMV strain Merlin-pAL1502, hits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Thus, the strong effect on PMN-mediated transmission of HCMV could be due to the fact that in the absence of pp65 or pp71, virions are either more poorly packaged or even released in lower numbers as mature virus particles from the infected donor cultures. During focal growth of the mutants in fibroblast monolayers, this circumstance might be overcome by the high multiplicity of infection that is observed for the cell-associated spread of HCMV [ 35 , 37 ]. Since we have demonstrated that the tegument proteins pp65 and pp71 contribute to the pathophysiologically relevant dissemination via leukocytes, the use of one of these proteins as a potential candidate for a future HCMV vaccine might be even more approachable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the strong effect on PMN-mediated transmission of HCMV could be due to the fact that in the absence of pp65 or pp71, virions are either more poorly packaged or even released in lower numbers as mature virus particles from the infected donor cultures. During focal growth of the mutants in fibroblast monolayers, this circumstance might be overcome by the high multiplicity of infection that is observed for the cell-associated spread of HCMV [ 35 , 37 ]. Since we have demonstrated that the tegument proteins pp65 and pp71 contribute to the pathophysiologically relevant dissemination via leukocytes, the use of one of these proteins as a potential candidate for a future HCMV vaccine might be even more approachable.…”
Section: Discussionmentioning
confidence: 99%
“…A soluble derivative thereof, PDGFRα-Fc, can bind to cell-free virions and inhibit entry into fibroblasts, endothelial and epithelial cells, but it could not inhibit PMN-mediated transfer [ 20 , 30 , 33 ]. In contrast to the failure of these large decoy receptors, smaller peptide fragments derived from the extracellular PDGFRα domains 1–3 [ 33 , 35 ] reduced the efficiency of virus transmission by PMNs when added either during the initial uptake step or during the subsequent transfer step [ 20 ]. Similar phenomena are observed for the spread of clinical HCMV isolates in fibroblast cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[92][93][94] In addition, scFv have been used against subunits of pentamer complex, 95 thus promising to be useful in the control of PMNL-mediated HCMV transmission. 96 By using: i) immortalised human endothelial cells 97 and human foetal fibroblasts; ii) PMNL derived from HCMV-seronegative blood donors; iii) the Merlin HCMV reference strain, 98 as a parental BAC clone comprising the entire wild-type HCMV genome; iv) four KO genes [UL128 (pentamer complex), UL74 (gO), UL83 (pp65), and UL82 (pp71)], which were generated by introduction into each gene of two stop codons, according to markerless mutagenesis, 99 the following results were obtained 90 in both directions of PMNL uptake and transmission.…”
Section: Interaction Of Endothelial Cells and Leukocytes In The Disse...mentioning
confidence: 99%
“…Cell culture-adapted strains, however, have at least partially lost this spread mode due to genomic alterations which mostly occur in the accessory proteins of the pentamer or in the RL13 locus [18,19]. gB and gH/gL complexes are required for both, the cell-free and the cell-to-cell spread as for example small inhibitors directed towards gO of the trimer [20,21] or towards gB [22] are able to inhibit both modes of spread. The pentamer can alternatively be used for cell-associated spread on fibroblasts and is sufficient for epithelial cell spread even without the presence of the trimer [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%